1983
DOI: 10.1055/s-2007-1017453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexamethasone on Cerebrospinal Fluid Monoamine Metabolites and Cortisol in Psychiatric Patients

Abstract: The effect of 1 mg dexamethasone on CSF levels of 5-hydroxyindoleacetic acid (5 HIAA), homovanillic acid (HVA) and cortisol (CS) was investigated in 100 psychiatric inpatients: 45 subjects had their lumbar punctures 1-4 days following dexamethasone administration, and the results were compared with those from 55 other patients investigated before drug ingestion. All patients were women, and none had received psychotropic medication for at least two weeks before the study. Seven subjects consented to two LPs bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Millard et al (1972) reported that IV administration of L-tryptophan to rats produced an increase in cerebral serotonin levels, and this increase was doubled by prior administration of corticosterone. Banki et al (1983) found increased levels of the serotonin-metabolite 5-hydroxyindoleacetic acid (5-HIAA) in cerebrospinal fluid after dexamethasone in a group of psychiatric patients. Similarly, Rothschild et al (1985) reported increased serotonin and 5-HIAA levels in the hypothalamus of rats after one dosage of dexamethasone IP.…”
Section: Discussionmentioning
confidence: 99%
“…Millard et al (1972) reported that IV administration of L-tryptophan to rats produced an increase in cerebral serotonin levels, and this increase was doubled by prior administration of corticosterone. Banki et al (1983) found increased levels of the serotonin-metabolite 5-hydroxyindoleacetic acid (5-HIAA) in cerebrospinal fluid after dexamethasone in a group of psychiatric patients. Similarly, Rothschild et al (1985) reported increased serotonin and 5-HIAA levels in the hypothalamus of rats after one dosage of dexamethasone IP.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a suppressive effect of glucocorticoids on PRL secretion. The relatively short duration of PRL suppression in DEX-treated rats is parallel to the time course of increased dopamine turnover [42]. The re bound increase in PRL observed might reflect the increase in serotonin turnover, which lasts longer than the dopaminergic effect [42].…”
mentioning
confidence: 84%
“…The relatively short duration of PRL suppression in DEX-treated rats is parallel to the time course of increased dopamine turnover [42]. The re bound increase in PRL observed might reflect the increase in serotonin turnover, which lasts longer than the dopaminergic effect [42]. Direct glucocorticoid effects or modulation of neurotransmitter-receptor functions might be involved in the attenu ated PRL responses to selective serotonin agonists after chronic cortisol treatment [43].…”
mentioning
confidence: 99%
“…Recently, strong GC immunoreactivity was found in all areas of the rat brain stem rich in 5-hydroxytryptamine (5-HT) cell bodies 118], The approximate coexistence of GC receptors and 5-HT neurons was reported by Fuxe et al 117] to be 100% in the B1-B9 brain stem raphe areas. After GC administration, changes in seroto nin (5-HT) metabolism have been shown in both rats (2K 30, 55] and humans [9]. GC administration has also been demon strated to reduce myoclonus responses to the 5- HT precursor, and behavioral responses to the 5-HT-releasing drug, /j-chloroamphetamine, and the nonselective 5- HT agonist,.…”
mentioning
confidence: 99%